The Resolution of Uncertainty in the Value and Probability Domains - Eungik Lee; Kathleen Ngangoue; Andrew Schotter (Center for Economic Studies and ifo Institute (CESifo), 2024)
We compare preferences for temporal resolution when uncertainty is resolved over a probability rather than a value. In various frameworks–e.g., Kreps and Porteus (1978)–, preferences over gradual versus one-shot resolution do not depend on whether values or probabilities define the main object of uncertainty. In our experiment, however, most subjects resolved uncertain values gradually but uncertain probabilities all at once–both in the gain and loss frames. This systematic discrepancy motivates an explanation for it that we call "process utility", which highlights the importance of information processing when deducing revealed preferences for temporal resolution from choice data.
Keywords: 330; resolution of uncertainty; probability; gradual resolution; one-shot resolution; process utility; non-instrumental information; Kreps-Porteus